Integration of Modern Pedagogical Technologies in the Development of Creative Thinking - Erkinov Ozodbek (INTERNATIONAL CONFERENCE ON MODERN RESEARCH AND SCIENTIFIC INNOVATION, 2026)
This article analyzes the role and importance of modern pedagogical technologies in the development of creative thinking. The study highlights the formation of students’ independent, innovative, and critical thinking skills through the use of interactive methods, information and communication technologies, project-based learning, and digital platforms in the educational process. In addition, the effectiveness of innovative pedagogical approaches and the integration of modern technologies in developing creative thinking are scientifically and theoretically substantiated. The research findings demonstrate that modern pedagogical technologies are an important factor in improving the quality of education and developing students’ creative potential.